PEMBUATAN REPOSITORI SKRIPSI MAHASISWA JURUSAN BUDIDAYA PERAIRAN FAKULTAS PERIKANAN DAN ILMU KELAUTAN UNIVERSITAS PATTIMURA: Creation Of Student Thesis Repository Majoring In Aquaculture, Faculty Of Fisheries And Marine Sciences, Pattimura University - Sophia N. M. Fendjalang; Krisye; Rahman Rahman; Nur T. Sirajuddin; Martha L. Wattimena; Yuliana Natan (Pakis Journal Institute, 2023)
The Aquaculture Department Library is an information service unit for library materials for students and lecturers who are required to provide information services that are fast, precise, relevant, useful for users. To further optimize the benefits of these sources of information, it is necessary to develop a library function in the form of a digital-based student thesis data storage facility. The purpose of this activity is to create a student thesis repository as an effort to facilitate student access to theses to obtain secondary scientific information in the Aquaculture Study Program at Pattimura University. The activity of creating a student thesis repository will be carried out in October – November 2022. The activities carried out include coordinating and extracting thesis data files to be uploaded, inputting data and files to Google Drive and the website, making posters and socializing the finished repository to students and lecturers majoring in Aquaculture and evaluating the effectiveness of student thesis repository. It can be concluded that the existence of a thesis repository for students of the Aquaculture Study Program can provide convenience to students and lecturers in finding information related to references, topics and research developments, especially in the field of Aquaculture.